Simulating hydrogen in fcc materials with discrete dislocation plasticity - Yu, H; Cocks, ACF; Tarleton, E (Elsevier, 2020)
We have performed discrete dislocation plasticity simulations of hydrogen charged microcantilever bend tests on an fcc material at realistic hydrogen concentrations. This was achieved by accounting for the near-core solute-solute interactions which was found to reduce the dislocation nucleation time and stress. Dislocation pile-ups were observed at the neutral mid plane of the cantilever, and hydrogen was found to increase the number of dislocations in the pile-ups. Meanwhile, hydrogen was observed to decrease the flow stress due to the reduced dislocation core force. This was in contrast to the first-order hydrogen elastic shielding mechanism which was found to be negligible at realistic concentrations. Local stress elevation was observed in the presence of hydrogen in simulations which included an obstacle close to the free surface of the microcantilever, indicating how hydrogen might induce premature stress controlled failure.